NEW YORK TAX - SHANNON,MJ; XX RON (Tufts Archival Research Center, 2007)
Marginalia; Memo regarding Governor Pataki's signing of legislation that would raise the tax on cigarettes by fifty-five cents in New York State. States that the New York Association of Convenience Stores held a meeting on how to respond to the tax. Includes recommendations on the necessary response in the media.